ANALISIS LAYANAN INFORMASI TENTANG PERKEMBANGAN SOSIAL REMAJA PADA SISWA KELAS VII SEKOLAH MENENGAH PERTAMA NEGERI 3 PONTIANAK - Lara, Resta; Yusuf, Abas; Lestari, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe Information service is a series of activities in order to provide assistance to students by providing information that can be used to make a further education plan. Therefore, the researcher wanted to know more about the information service by the guidance and counseling teacher on the development of adolescent social in class VII SMP Negeri 3 Pontianak. The problem of this research is "What is the information service by the tutor teacher about the social development of adolescents in class VII SMP Negeri Pontianak?". This study generally aims to obtain a benchmark for information services by the mentor teacher about the social development of adolescents in class VII SMP Negeri 3 Pontianak?. The method used is descriptive method with a quantitative approach namely problem solving procedures by describing the relationship of information services with social development of adolescents in class VII SMP Negeri 3 Pontianak. Statistically and descriptively explained. The sample in this study were 89 students of class VII SMP Negeri 3 Pontianak. Data collection techniques in this study are direct communication techniques and indirect communication techniques. Data collection tools in this study were questionnaires, and teacher counselor interviews. Based on the results of data analysis showed that the information service about social development of adolescent students of class VII SMP Negeri 3 Pontianak reached 57.11%, the achievement was in the "less" range.Â Keywords: information services, adolescent social development.Â